THE EFFECT OF BRANDING, PRODUCT QUALITY, AND REFERENCE GROUP ON PURCHASING DECISIONS THROUGH PROMOTION AS INTERVENTION VARIABLES (CASE STUDY OF SAMSUNG CUSTOMER AT METEOR CELL STORE MALANG) - Sudirman Sudirman (MAGISTER MANAJEMEN UNISMA, 2020)
AbstractBranding, product quality, reference group, and promotion is one that influences purchasing decisions. Buyers who have a high brand image will lead to purchasing decisions.This research was conducted at the Meteor Cell Store Malang. The purpose of this study was to examine and analyze the effect of branding on promotion, product quality on promotion, reference group on promotion, branding on purchasing decisions, product quality on purchasing decisions, reference groups on purchasing and promotion decisions on purchasing decisions.The variables used in this study are branding, product quality, and reference group as endogenous variables. Exogenous variables are purchasing decisions and the intervening variable is a purchasing decision. The samples used in this study were Meteor Cell Store Malang's customers who bought Samsung Brand Smartphones, as many as 95 respondents. The data collection method used is a questionnaire. The analysis used includes the instrument test, classic assumption test, normality test and hypothesis test using path analysis with the help of SPSS 21.0 For Windows.The results of this study indicate that branding and product quality have a significant and positive direct effect on promotion, while the benchmark group variable does not directly influence promotion. The brand image variable and product quality have a significant and positive effect on purchasing decisions, while the reference group variable has no effect on purchasing decisions. This shows that the reference group is no longer needed by consumers of the Meteor Cell Store Malang, they prefer to find information about Samsung smartphones via the internet and other information when viewed from the respondents' educational background for they are on average are graduate students. Keywords: Branding, Product Quality, Reference Group, and Purchasing Decision.